Peran Asean Political Security Community (APSC) Dalam Mengontrol Peredaran Senjata Ringan Kaliber Kecil (SRKK) Illegal Di Kawasan Asia Tenggara - Peni Aprilianti Sekaringrum; Aumita Kirana Putri; Ratri Aviyanti (Universitas Negeri Surabaya, 2020)
ASEAN as a regional organization in Southeast Asia plays a role in maintaining security in the region, the current security issues that go beyond the national borders requires cooperation between countries in the region to overcome solid. The problem of the circulation of illegal small arms light weapons interconnected with drug trafficking and other security problems that it becomes an important issue that must be addressed in the form of security kawasan. One of role of ASEAN is through the ASEAN Political Security Community that focuses on creating and maintaining regional Southeast Asian conflict-free stail security. Through the existence of regional organizations is the one of each member state of mutual trust and work together to address transnational security issues, with the APSC ASEAN to perform its role as a regional organization. This study aims to look at how the process of cooperation that occurs among ASEAN member countries to create a stable regional security in accordance with the principles contained in the Declaration of ASEAN and the ASEAN Charter Bangkok. Researchers also want to know whether the role of ASEAN through the formation of APSC produce positive results for addressing regional security issues that can be resolved only running by the state. To achieve this, the researchers used the theory of roles, and concepts such as international organizations, the role of international organizations, international regimes are also cooperative security. The method used in this study is a qualitative research method with a descriptive case study technique, techniques of data collection using interviews and literature studies. The results of this study indicate that although the role of ASEAN has been run by the APSC but the results shown on the formation of APSC until now did not show any significant eduction and effectiveness have not seen real APSC.